Longitudinal internal training load and exposure in a high-performance basketball academy - Lever, J. R.; Duffield, R.; Murray, A.; Bartlett, J. D.; Fullagar, H. H. K. (The Journal of Strength and Conditioning Research, 2024)
This study describes the longitudinal training exposure (session counts) and internal training load (Rating of Perceived Exertion [RPE] and Session Rating of Perceived Exertion [sRPE]) of youth basketball players at a high-performance academy, based on the training year, training term, and playing position. Historical internal training load and training exposure data were collated from 45 male high-performance youth basketball athletes between 2015 and 2019. Data included session duration, RPE, sRPE, training type, and date. Linear mixed models and pairwise comparisons were performed on the weekly means and categorized by training year (year 1, year 2, year 3), term (term 1, term 2, term 3, term 4), and playing position (Backcourt, Frontcourt). Linear mixed models indicate that the individual athlete had the greatest influence on variance in training load and exposure. Significant differences were observed for increased session count, duration, and sRPE (p < 0.001) in year 2 compared with year 1. These measures also increased within each year whereby term 3 and term 4 (p < 0.001) were significantly greater than term 1 and term 2. No significant differences were observed between playing position (p > 0.05). Training exposure and internal training load increase in year 2 from year 1 for high-performance youth basketball academy athletes. Differences between training load and exposure for terms (i.e., training blocks) suggest the phase of season influences training prescription, while playing position has limited effect.